Genetic Associations with Age-related Macular Degeneration and Genetic Risk Score in the Epidemiologic Coimbra Eye Study - Farinha, Claudia (2022)
Introduction: To date several genetic variants are known to play an important role in age-related macular degeneration(AMD). Variations in the genetic pool of different populations impact the disease prevalence, incidence and risk of progression. This report aims to determine the genetic contribution in the development of AMD in a Portuguese population from the Coimbra Eye Study (CES,NCT01298674,NCT02748824), and to determine the genetic risk score(GRS). Methods: Participants in the CES underwent ophthalmologic examination and imaging in baseline and 6.5-year follow-up visits. AMD staging was performed in a centralized reading center. Two genetic analyses were performed, a case-control analysis and a progression to AMD analysis. Genomic DNA was isolated from blood samples collected in the follow-up visit. Genetic sequencing was performed using the EYERISK assay under the European Eye Epidemiology Consortium (E3). Sixty-nine single nucleotide polymorphisms (SNPs) were genotyped and tested for association under an additive model with presence/absence of AMD in the follow-up visit, and with progression/no progression in the longitudinal analysis. Logistic regression analysis was performed to assess allelic odds ratio at 95% CI for each variant, adjusted for age and sex. GRS were calculated for AMD cases/controls and progressors/non-progressors.  Results: In case-control analysis samples from 237 patients and 640 controls were included. The SNPs associated to increased risk of AMD were: ARMS2 rs10490924, ARMS2/HTRA1 rs3750846,CFH rs35292876,SLC16A8 rs8135665,TGFBR1 rs1626340. The SNPs with protective effect were: CFH rs10922109, CFH rs1410996,C2/CFB/SKIV2L rs429608,CETP rs5817082,CNN2 rs10422209,CFB rs641153 and RDBP_CFB rs760070. In progression to AMD analysis (630 non-progressors and 137 progressors), identified risk-variants for progression were: ARMS2 rs10490924, ARMS2/HTRA1 rs3750846,CFH rs35292876; and protective variants were C2_CFB_SKIV2L rs429608,CFH rs10922109,CFH rs1410996,CNN2 rs10422209,CFHR5 rs10922153,SYN3/TIMP3 rs5754227,COL10A1 rs3812111. The GRS for AMD cases and controls was 1.12±1.19 and 0.65±1.12 (p<0.001), and for progressors and non-progressors was 1.19±1.18 and 0.67±1.14 (p<0.001). Conclusion: This is the first genetic study in AMD in a Portuguese population.  Similar variants were found to be associated with the presence and progression to AMD in our epidemiological study, while others were protective. The GRS was significantly different between cases and controls showing its potential when assessing risk. Genetic characterization is important to pursue in different populations to further expand the knowledge of AMD pathophysiology.